FACTORS INFLUENCING THE OCCURRENCE OF ISPA IN TODDLER IN THE WORK AREA OF THE KAMPALA COMMUNITY HEALTH CENTER UPTD, SINJAI REGENCY IN 2026 - Alfiah; Kamrianti Ramli (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
ISPA is a respiratory disorder caused by infectious pathogens such as bacteria, viruses, rickettsia, fungi, and parasites that can be transmitted through droplets of fluids. ARI is one of the diseases that contributes to the highest morbidity and mortality rates in toddlers. The purpose of this study was to determine what factors influence the incidence of ISPA in toddlers in the Kampala Community Health Center work area of ​​Sinjai Regency in 2025 based on cigarette smoke exposure and immunization status. This research method uses an observational analytical quantitative research method with a cross-sectional study approach. The sample in this study were all mothers who had children aged 12-59 months who experienced ISPA as many as 31 respondents. Data collection was carried out using a questionnaire. The collected data was processed and analyzed using the SPSS program and analyzed using the Chi-square test. The results of the study were that there was a significant relationship between exposure to cigarette smoke and the incidence of ISPA in toddlers (p-value = 0.00 OR 12.667) and there was a relationship between immunization status and the incidence of ISPA in toddlers with a total value (p-value = 0.045, OR 9.600) in the Work Area of ​​the Kampala Health Center UPTD, Sinjai Regency in 2025. The high incidence of ARI was influenced by several factors such as exposure to cigarette smoke and immunization status in toddlers.